Pilot Randomized Controlled Trial of a Novel Smoking Cessation App Designed for Individuals With Co-Occurring Tobacco Use Disorder and Serious Mental Illness. Issue 9 (31st October 2019) - Vilardaga, Roger; Rizo, Javier; Palenski, Paige E; Mannelli, Paolo; Oliver, Jason A; Mcclernon, Francis J
Abstract: Introduction: High rates of tobacco use among people with serious mental illness (SMI), along with their unique needs, suggest the importance of developing tailored smoking cessation interventions for this group. Previous early-phase work empirically validated the design and content of Learn to Quit, a theory-based app designed for this population. Methods: In a pilot randomized controlled trial, we compared the feasibility, acceptability, and preliminary efficacy of Learn to Quit versus QuitGuide, an app designed for the general population. All participants received nicotine replacement therapy and technical assistance. Daily smokers with SMI ( N = 62) participated in the trial with outcomes assessed at weeks 4, 8, 12, and 16. Results: Compared to QuitGuide, Learn to Quit participants had similar number of days of app use (34 vs. 32, p = .754), but larger number of app interactions (335 vs. 205; p = .001), longer durations of app use (4.24 hrs. vs. 2.14 hrs; p = .044), and higher usability scores (85 vs. 79, p = .046). At week 16, Learn to Quit led to greater reductions in cigarettes per day (12.3 vs. 5.9 for QuitGuide; p = 0.10). Thirty-day point prevalence abstinence was verified in 12% of Learn to Quit participants versus 3% of QuitGuide participants (odds ratio = 3.86, confidence interval = 0.41 to 36, p = .239). Changes in psychiatric symptoms and adverse events were not clinically significant between conditions. Conclusions: This pilot trial provides strong evidence of Learn to Quit's usability, feasibility, and safety. Preliminary evidence suggests the app may be efficacious. A randomized controlled efficacy trial is needed to test the app in a larger sample of smokers with SMI. Implications: This study suggests that the Learn to Quit app is a feasible approach to deliver smoking cessation treatment in patients with co-occurring tobacco use disorder and SMI. This means that, if found efficacious, this technology could be used to deploy smoking cessation treatment to larger segments of this population, hence improving public health. Therefore, a randomized controlled trial should be conducted to examine the efficacy of this digital intervention.